Work posture analysis using ovako working postural analysis system (OWAS) on workers at PT INKA (Persero) - Suseno, Wahyu (BKM Public Health and Community Medicine, 2021)
Background: One of the occupational diseases caused by non-ergonomic work processes is musculoskeletal complaints. It is a disease that occurs in body structures, such as muscles, joints, tendons, ligaments, nerves, bones, and the local circulatory system by occupational factors. PT INKA (Persero) is an industry engaged in inland transportation, especially railways with high potential and danger factors. Even though PT INKA (Persero) Madiun has lifting and transportation equipment, such as strollers, forklifts, cranes, and mines, there are still some manual handling jobs. Effective working days in one week are five working days. Data from the INKA Clinic (Polinka) in 2019 showed 3-4 workshop workers suffering from low back pain every month. The author realized the necessity to study ergonomics and MSDs complaints at PT INKA (Persero) Madiun. Research objectives: This study aimed to determine workshop workers' work posture at PT INKA (Persero) Madiun. Research Methods: This was a quantitative study using a cross-sectional approach that aimed to determine the dynamics of work posture effect on MSDs complaints at one time. Work posture assessment using the Ovako Working Posture Analysis System (OWAS) method, along with other variables such as age, smoking, working period, and duration of work to measure complaints of Musculoskeletal Disorders (MSDs) in 36 workshop workers of the Bogie PMK unit. The research data were analyzed and interpreted using Statistical Stata 13. Bivariate data analysis used Kendall's tautest. Results and Discussion: The workshop workers' Musculoskeletal Disorders (MSDs) complaints in the PMK Bogie Unit resulted from work posture and working period. When the exposure intensity level was high beyond the tolerance of the worker's body ability, it could result in fatigue felt by tired workers. Based on the assessment using the Ovako Working Postural Analysis System (OWAS) method, it is necessary to improve, especially on Macro Reforming, A Drilling, Grinding, and Welding work. This work posture was a risk of ergonomic hazards. The working conditions and work equipment used by workers were not per the worker's body posture, resulting in excessive muscle stretching, which led to complaints of Musculoskeletal Disorders (MSDs). Conclusion: There was a risk of ergonomics hazard due to a mismatch between the equipment used by workers and working conditions with the worker's body size.